Feasibility Analysis of Grilled Meatball Business in the Retention Pond Area of Kendari City Boulevard - Hanif, Listi Arfiani; Alwi, La Ode; Zani, Munirwan (International journal of technology and education research, 2025)
This study aims to analyze the revenue and feasibility of a grilled meatball business run by micro-entrepreneurs in the Boulevard Retention Pond Area, Kendari City. This study uses a quantitative descriptive approach. The sample in this study consisted of 10 respondents, representing all grilled meatball businesses in the location, determined using a census technique. The data used consisted of primary data obtained through direct observation and interviews, as well as secondary data from related literature. The results show that the average total costs incurred by entrepreneurs were Rp8,791,838 per month, while the average revenue was Rp14,250,000 per month, resulting in an average net income of Rp5,458,163 per month. A feasibility analysis using the Revenue Cost Ratio (R/C) method showed an R/C value of 1.62, meaning that every Rp1 of costs generated Rp1.62 in revenue. Therefore, the grilled meatball business in this area is deemed feasible because it is capable of generating profits for the business owner